Depression symptom trajectories among mothers living with HIV in rural Uganda - Familiar, Itziar (AIDS Behav, 2019)
The aim was to identify latent class trajectories of depression symptoms among HIV+ women in Uganda. Depression was assessed at four time points using the Hopkins Symptom Checklist among 288 women caring for a child 2–5 years old. Mixture modeling was used to estimate the number and nature of classes defined by trajectories of depressive symptoms over time. Maternal and child characteristics were explored as predictors of class. Three trajectories of symptoms of depression were identified; 1) stable-low, 2) moderate-subclinical, and 3) chronic-high. About 8% of women reported moderately or highly elevated symptoms at the first assessment and consistently onward (i.e. chronically). Higher anxiety levels, less social support, more functionality problems, and more executive behavior problems in children predicted membership in the moderate-subclinical and chronic-high classes. Identifying patterns of depression trajectories can help target intervention efforts for women who are likely to experience the most chronic and impairing symptomatology.